2018
DOI: 10.3390/su10082738
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of the Economy in Young Adults’ Understanding of Sustainable Development

Abstract: Abstract:The economic dimension is one of the central perspectives in both sustainable development and education for sustainable development. The role of the economy in sustainable development has been discussed extensively over the years and different views exist about how economic activities affect other sustainability dimensions. How young people view the relationships among economic perspectives and sustainable development seems to be an underemphasized perspective in sustainability education and underexpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In the above-mentioned previous study, we investigated how upper secondary students in Sweden view the interconnectedness of economic objectives and SD (Berglund and Gericke 2018). We focused specifically on the concepts of economic growth and economic development, and students' views of their interconnectedness to SD.…”
Section: Student' Views On the Economic Dimension Of Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above-mentioned previous study, we investigated how upper secondary students in Sweden view the interconnectedness of economic objectives and SD (Berglund and Gericke 2018). We focused specifically on the concepts of economic growth and economic development, and students' views of their interconnectedness to SD.…”
Section: Student' Views On the Economic Dimension Of Sustainable Developmentmentioning
confidence: 99%
“…In a previous quantitative generalizable study, we identified four distinctively different belief sets among grade 12 students regarding the interconnections between economic objectives and SD. More specifically, students' views on the role of economic growth and economic development in SD were investigated, and each of the four belief-groups was characterized by a specific way of viewing the interconnections between economic perspectives and SD (Berglund and Gericke 2018). In this study, we move on to investigate the diversity of views in depth by focusing on students' motivational arguments for the different views present within these four groups.…”
Section: Introductionmentioning
confidence: 99%
“…Currently in the world, many different city, country, and regional rankings are being used to present various kinds of information about sustainable development and corporate social responsibility (CSR) [21,[38][39][40][41][42][43][44][45][46]. However, these rankings concentrate on the NTS-3 level or higher, or exclusively on metropolitan areas.…”
Section: Creative Industries Sustainability and Local Governmentsmentioning
confidence: 99%
“…At a general level, there is, for example, a discussion about whether the goals of economic growth and environmental sustainability are compatible, a discussion relating to over-consumption, over-exploitation of nature's resources and the impact on the regenerative capacity of ecosystems (e.g., Munda 1997;Ekins 2000;Aşici 2013). A recent study investigated how young adults in Sweden view the relationships between economic growth, economic development and SD and found a number of different ways that young people view these relationships (Berglund and Gericke 2018). In addition, the multidimensionality of SD gives rise to different interpretations among people or groups with respect to what is regarded as sustainable in specific situations (Rauch 2002;Jickling and Wals 2008).…”
Section: Sustainable Development Education and Culturementioning
confidence: 99%